Evaluation of Treatment Outcomes for Mobile Tongue Cancer at K Hospital from 2020 to 2023 - Van Manh, Khong; Dang Khanh, Pham; Duc Loi, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 1DO - 10.25073/2588-1132/vnumps.4673, 2025)
This study presents a cross-sectional descriptive analysis of 150 patients (male: 74.7% and female: 25.3%, mean age: 56.1 ± 11.8) with mobile tongue cancer treated at Hospital K between 2020 and 2023. This study aimed to assess the treatment outcomes of tongue cancer at Hospital K during the specified period. Results revealed that most cases were managed surgically (64.7%). The overall survival rate (OS) after 3 years was high (67.7%), with a mean survival time of 40.6 ± 1.4 months. Simple surgery exhibited the highest OS at 3 years (81.6%), significantly outperforming chemo/radiotherapy combined (p < 0.01). Patients diagnosed at early stages, with primary tumors at stages T1 and T2, and without lymph node metastasis, had significantly higher OS rates at 3 years compared to those diagnosed at later stages, with tumors at stages T3, T4, or with lymph node metastasis (p < 0.01). After initial treatment, 33 patients experienced recurrence (22%), predominantly in cervical lymph nodes (81.8%), and 6 patients developed distant metastases. Therefore, early disease diagnosis and appropriate treatment strategy selection are crucial as they contribute to extended patient survival time.